Sistem Informasi Pengelolaan Donasi Sembako Panti Asuhan Menggunakan Metode Simple Additive Weighting - Saragih, Harianto; Harahap, Aninda Muliani (STMIK Budi Darma, 2024)
In this modern era, the development of technology and information systems greatly affects various sectors, including social sectors such as orphanages. This research aims to develop a Food Donation Management Information System at Orphanages using the Simple Additive Weighting (SAW) method. The SAW method was chosen because of its ability to simplify the complexity of multi-criteria assessments by giving weights to each criterion and determining the best alternative based on the weighted sum of the performance ratings on each attribute. This research applies descriptive quantitative methods by collecting data through observation, interviews, and literature studies. System development uses the Waterfall model which involves the stages of needs analysis, design, implementation, testing, and maintenance. In this case study, seven orphanages in Deli Serdang were assessed based on the criteria of access to location, routine programs, facilities, and number of children. The results show that by applying the SAW method, the developed information system can help orphanage managers in making better decisions, stock monitoring, distribution planning, and optimizing the use of resources. The weight values for the criteria are determined as follows: C1 = 0.1, C2 = 0.2, C3 = 0.3, and C4 = 0.4. The final ranking shows that the best alternative is the orphanage coded A7 with the highest score of 0.855. Thus, this information system is expected to be an effective model for donation management in orphanages, increase transparency and accountability, and support the welfare of children in orphanages through more efficient management of basic necessities.